Cranial MRI Findings in Predicting the Severity of Hypoxic-Ischemic Encephalopathy in Term Neonates - Mehmet Coşkun; Oğuz Han Kalkanlı; Rüya Çolak; Senem Alkan Özdemir; Tülin Gökmen Yıldırım; Şebnem Çalkavur; Fazıl Gelal (Galenos Publishing House, 2021)
Objective: The aim of this study is to compare magnetic resonance imaging (MRI) findings with severity of hypoxic-ischemic encephalopathy (HIE) in term neonates. Methods: Sixty-three newborns with HIE in whom cranial MRIs were performed within the first 3 weeks of life between 2016 and 2020 were included in the study. Severity of HIE was graded using Sarnat & Sarnat staging. In statistical analysis, Stage 1 was considered as mild, Stage 2 or 3 as severe HIE. The signal intensities of perirolandic cortex, posterior limb of internal capsule (PLIC), globus pallidus, and cerebrospinal tract on T1- weighted imaging (T1WI), and of perirolandic cortex, PLIC, ventrolateral thalamus, lateral edge of putamen and tegmentum on T2WI, and brain diffusion weighted imaging (DWI) findings were evaluated with consensus by two radiologists blinded to clinical findings. Gestational age, birth weight and MRI signal intensities were compared with HIE groups using t test, and Fisher-Exact test. Results: There were 31 and 32 infants with mild and severe HIE, respectively. Gestational age and birth weight were not different between mild and severe HIE groups. The number of cases with abnormal signals in PLIC and globus pallidus on T1WI, and PLIC on T2WI were significantly higher in severe HIE (p=0.022, p=0.008, and p=0.032, respectively). The presence of signal abnormality in other regions and DWI were not significantly different between HIE groups. Conclusion: Cranial MRI may play a remarkable role in determining pattern and severity of HIE. Signal abnormality in PLIC and globus pallidus may suggest severe HIE in term neonates.